Causal Association Between Lung Cancer and Rash: A Bidirectional Mendelian Randomization Study - Yang Xiao; Tian-Tian Li; Ming Li Yuan; Wen Yin; Jing Zhu (Clinical Medicine Insights: Oncology)
Background: Skin involvement is one of the many clinical manifestations of lung cancer patients. However, there are fewer in-depth studies exploring the causal relationship between skin rashes and lung cancer subtypes, and the causal relationship is unknown. This study aims to explore the potential causal relationship between rash development and lung cancer diagnosis. Methods: From the Genome-wide Association Studies (GWAS) database, we sourced comprehensive data on skin rash, lung cancer, and gene expression Quantitative Trait Loci (eQTL). Drawing from this, we conducted a comprehensive analysis that integrated Mendelian Randomization (MR), protein-protein network analysis, and enrichment analysis to explore the causal relationship and potential mechanisms between rash and lung cancer. Results: This study reveals an increased risk of rash in small and squamous cell lung cancer patients, with odds ratios of 1.08 and 1.26, respectively. However, no causal link between rash and lung cancer was found. Genetic analysis identified 3 genes positively associated with both conditions and 6 negatively associated, suggesting complex genetic interactions. Sensitivity analysis did not indicate heterogeneity or pleiotropy. Conclusions: Our study shows that squamous cell lung cancer patients are more likely to get skin rashes. But the rash is not directly linked to lung cancer. Future research should explore rashes as a therapeutic target and prognostic indicator.